Determination of 55Fe/58Fe and 59Fe/58Fe isotopic ratios in irradiated Na2/FeNO/CN/5/.2H2O by SSMS (spark source mass spectrometry) - Lukaszew, R. A.; Marrero, J. G.; Cretella, R. F. (Springer Science, 1986)
Fil: Lukaszew, R. A. Comisión Nacional de Energía Atómica; Argentina